Desenvolvimento e validação de um novo método analítico para quantificação de resíduo de eprinomectina no leite bovino - Ré Filho, Antonio Oscar (Universidade Federal de São Carlos, 2016)
Brazil is one of the biggest producers and consumers of milk around the globe. To ensure the productivity and profitability of the cattle, the use of antiparasitic plays an important role in strategic control of worm infections in dairy cows. The justification for such effect on milk’s production is based on the reduced appetite of infected animals caused by gastrointestinal nematodes. As known, any reduced appetite has a major impact on the production of dairy cow. Eprinomectin is an antiparasitic that has been used in dairy cows, however, the use of this product should be done properly respecting its withdrawal period, so that it is impossible to find its residue in milk above their Maximum Residue Level (MRL). In order to ensure consumer’s safety, national and international agencies have set Maximum Residue Level. Thus, this study aims at the development and validation of an analytical method for the determination of Eprinomectin residue in milk (EPRI) by liquid chromatography coupled with sequential mass spectrometry with electrospray ionization (LC-ESI-MS / MS), and subsequent determination of the withdrawal period of the veterinary drug from Ouro Fino Saúde Animal. The residual depletion study is necessary for the veterinary medicinal product registration in the Ministry of Agriculture, Livestock and Supply (MAPA). Ivermectin (IVER) was used as internal standard in the analytical method. In development of the extraction method it out a comparative study was carried out in terms of recovery between QuEChERS and liquid-liquid methods with low temperature partition (ELL-PBT). The optimization of the two extraction methods was made by factorial design. The best recovery was observed in ELL-PBT method. Acetonitrile was used as extractor solvent, the partition phase between organic and aqueous phase was made by freezing the samples at -20 ° C for 12 hours and in the clean up step hexane was used as solvent. The analytical validation parameters will be evaluated according to standards established by the Guarantee Manual of Analytical Quality of MAPA (MAPA/ ACS, 2011). The method was linear for eprinomectin in the range of concentration of 10.0 to 50.0 ug L-1, the linear correlation coefficient (r) was in accordance with the guidelines for bioanalytical methods (r ≥ 0,98). The repeatability was evaluated in three levels of fortification being performed for three consecutive days. Good intra-laboratory reproducibility was obtained, with coefficient of variation (CV) of 8,6 % for the fortification of MRLS. The recovery was above 80.0% for the three levels of fortification, being of 94.8 % for the level of MRLS. Satisfactory values for the decision limit (CCα) and detection capability (CCβ) were obtained, being CCα 22,1 µg L-1 and CCβ 24.2 µg L-1. The limits of detection (LOD) and the limits of quantification (LOQ) were determined from the data of the calibration curve. The LOD showed the value of 1.9 ug L-1 and the LQ of 5.9 UG L-1. Thus, the value of LOQ was below the MRL and of the first level of concentration of the analytical curve.
Development and validation of a new analytical method for the quantification of eprinomectin residue in bovine milk
Keywords: Resíduos; Eprinomectina; Resíduos; Leite; Eprinomectin; Residues; Milk; LC-ESI-MS/MS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA